Intracellular Redox Perturbation in Saccharomyces cerevisiae Improved Furfural Tolerance and Enhanced Cellulosic Bioethanol Production - Liu, Chen-Guang; Li, Kai; Li, Ke-Yi; Sakdaronnarong, Chularat; Mehmood, Muhammad Aamer; Zhao, Xin-Qing; Bai, Feng-Wu (Frontiers in Bioengineering and Biotechnology, 2020)
Being a major toxic byproduct found in the hydrolysate of lignocellulosic biomass, furfural inhibits the growth and ethanol fermentation of Saccharomyces cerevisiae. The current study was focused on intracellular redox perturbation caused by cofactor availability on furfural tolerance. Three strategies were employed in cofactor conversion in S. cerevisiae: (1) heterologous expression of NADH dehydrogenase from E. coli which catalyzed the NADH to NAD+ and increased the cell sensitivity to furfural, (2) overexpression of GLR1, OYE2, ZWF1, and IDP1 genes which are involved in NADPH and NADP+ interconversion, and enhanced tolerance S. cerevisiae, (3) overexpression NAD(P)+ transhydrogenase (PNTB) and NAD+ kinase (POS5) which showed a little impact on furfural tolerance. Overall, the expression of cofactor-related genes caused a large redistribution of metabolic fluxes. The overexpression of transhydrogenase increased glycerol yield, but showed no significant impact on either of glucose, ethanol or acetate yield. However, the overexpression of glutathione oxidoreductase (GLR1) or glucose-6-phosphate dehydrogenase (ZWF1) increased ethanol and glycerol yield but decreased acetate yield. These results indicated that the availability of NADPH plays a very important role in furfural tolerance.